Cloud Service Selection Using Integrated Approach Of Fuzzy AHP And Fuzzy Topsis - Pavani, S; Shukla, R (International Journal of Computer Sciences and Engineering, 2025)
Cloud computing has emerged as a new computing platform for providing fast and low cost services to the individual ,organizations ,government etc. over the internet and is a future generation technology. Cloud computing model means to increase the opportunities for cloud user by accessing leased infrastructure and software application from anywhere and anytime manner. Cloud computing mainly consist there service model as Software as a Service (Saas), Platform as a Service (PaaS) and Infra structure as a Service (IaaS). These service models are being provided by many cloud services provider and a user can choose any one of them based on various parameters .which many differ from one service provider to another service provider and is a challenging and tedious task for an end user to select the best one. This paper provides an approach to select cloud services among the available alternatives to the IT users using two popular Multi Criteria Decision Making (MCDM) Techniques: Fuzzy Analytical Hierarchy Process (FAHP) and Fuzzy Technique for Order Preference by Similarity to Ideal Solution(FTOPSIS) with special reference to triangular fuzzy membership function for experimental hypothetical alternatives as and services are considered with identified criteria. Selection process MCDM techniques are enough capable to find out the best alternatives as cloud service, a hypothetical cloud services as alternatives, used on identified criteria where ranked and found satisfactory